2017
DOI: 10.3892/or.2017.5769
|View full text |Cite
|
Sign up to set email alerts
|

Centromere protein U is a potential target for gene therapy of human bladder cancer

Abstract: To investigate the role of centromere protein U (CENPU) in human bladder cancer (BCa), CENPU gene expression was evaluated in human BCa tissues. We used real-time quantitative PCR (qPCR) and found that CENPU gene expression in human BCa tissues was higher compared to that observed in cancer-adjacent normal tissues. High CENPU expression was found to be strongly correlated with tumor size and TNM stage. Kaplan-Meier survival analysis indicated that high CENPU levels were associated with reduced survival. We use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 29 publications
2
24
0
Order By: Relevance
“…Studies have revealed that CENPU upregulation is correlated with progression and prognosis in luminal breast cancer, 56 familial colorectal cancer, 57 and bladder cancer. 58 Additionally, CENPU promotes prostate cancer cell proliferation and colony formation and significantly inhibits apoptosis; however, no clear change in CENPU expression has been identified. 59 Moreover, no data are available regarding the oncogenic role and clinical significance of CENPU in lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have revealed that CENPU upregulation is correlated with progression and prognosis in luminal breast cancer, 56 familial colorectal cancer, 57 and bladder cancer. 58 Additionally, CENPU promotes prostate cancer cell proliferation and colony formation and significantly inhibits apoptosis; however, no clear change in CENPU expression has been identified. 59 Moreover, no data are available regarding the oncogenic role and clinical significance of CENPU in lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical relevance analysis suggested that MLF1IP (also known as CENPU) and ITGB4 were significantly correlated with shorter overall survival. Role of MLF1IP had been preliminarily elucidated in some cancers including bladder cancer, ovarian cancer and prostate cancer, while little is known in PDAC progression [33–35]. The precise function of MLF1IP in PDAC need to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Hub genes and their corresponded target miRNAs are presented in Table . Finally, 31 miRNAs, whose functions were correlated with tumor progression (Chang et al, ; Chang et al, ; Chen et al, ; Gao et al, ; Gu et al, ; Han et al, ; He et al, ; Kucuksayan et al, ; Li, Ma, Zhang, Ji, & Jin, ; Li, Ran, et al, ; Li & He, ; Li, Fu, et al, ; Li, Cui, Li, Zhang, & Li, ; Liu et al, ; Liu, Liu, Deng, et al, ; Liu, Liu, & Lu, ; Liu, Liu, Zhang, Tong, & Gan, ; Liu, Miao, et al, ; Luo et al, ; Tang et al, ; Wang et al, ; Wang, Cao, Su, Li, & Yan, ; Wu et al, ; Wu, Mo, Wan, Dan, & Hu, ; Xia, Jing, Li, & Lv, ; Xu et al, ; Zeng et al, ; Zhang, Hao, et al, ; Zhang et al, , ; Zhu et al, ), drug resistance (Bian et al, ; Gao et al, ; Lin, Xie, Lu, Hu, & Chang, ; Pan, Chen, Shen, & Tantai, ; Su et al, ; Xu et al, ; Zhou, Wang, & Feng, ), radiosensitivity (Liu, Li, & Gao, ), recurrence (Sim et al, ) or autophagy (Pan et al, ) in lung cancer, were identified (Table ).…”
Section: Resultsmentioning
confidence: 99%